Single molecule protein stabilisation translates to macromolecular mechanics of a protein network. Issue 27 (24th June 2020) - Hughes, Matt D. G.; Cussons, Sophie; Mahmoudi, Najet; Brockwell, David J.; Dougan, Lorna
Abstract : Folded globular proteins are attractive building blocks for biomaterials as their robust structures carry out diverse biological functions. These biomaterials are ideal to study the translation of molecular properties to multi-molecular assemblies. Abstract : Folded globular proteins are attractive building blocks for biopolymer-based materials, as their mechanically resistant structures carry out diverse biological functionality. While much is now understood about the mechanical response of single folded proteins, a major challenge is to understand and predictably control how single protein mechanics translates to the collective response of a network of connected folded proteins. Here, by utilising the binding of maltose to hydrogels constructed from photo-chemically cross-linked maltose binding protein (MBP), we investigate the effects of protein stabilisation at the molecular level on the macroscopic mechanical and structural properties of a protein-based hydrogel. Rheological measurements show an enhancement in the mechanical strength and energy dissipation of MBP hydrogels in the presence of maltose. Circular dichroism spectroscopy and differential scanning calorimetry measurements show that MBP remains both folded and functional in situ . By coupling these mechanical measurements with mesoscopic structural information obtained by small angle scattering, we propose an occupation model in which higher proportions of stabilised, ligand occupied, protein building blocks translate their increased stability to the macroscopic properties of the hydrogel network. This provides powerful opportunities to exploit environmentally responsive folded protein-based biomaterials for many broad applications.